DSC analysis and evaluation of forces released on deactivation of 0.40-mm (0.016") orthodontic thermo-activated NiTi wires: An in vitro study - Vítor Marques Sapata; Diogo Marques Sapata; Julio Araújo Gurgel; Antônio Medina Neto; Adilson Luiz Ramos (Tabriz University of Medical Sciences, 2020)
Background. This study evaluated the phase transformation of NiTi orthodontic wires and forces they release on deactivation. Methods. The structural phase transformations of the following five thermo-activated nickel-titanium (NiTi) wires were evaluated using differential scanning calorimetry (DSC): Flexy Thermal Sentalloy® (GAC International), NiTi (35ºC) (Eurodonto), Thermo-Plus® (Morelli), FlexyNiTi® Flexy Thermal (35ºC) (Orthometric) and Damon® CuNiTi (35ºC) (ORMCO Corp.). The wires had a cross-section of 0.40 mm (0.016"). In addition, the forces they released were investigated using the three-point bending test. Five arches of each wire were tested using DSC (-20/80ºC at 10ºC/min), and six arches from each wire were sectioned for bending tests. The data were analyzed with ANOVA and post hoc Tukey tests. Pearson's correlation test was performed between the results yielded by the DSC tests and those by three-point analyses (P=0.05). Results. The DSC analysis showed differences between the NiTi alloys from all the manufacturers, with no differences between the lots of the same brand. ORMCO and Orthometric wires exhibited similar TTR values in cooling (P=0.49), and statistically similar TTR values in heating (P=0.056). The three-point bending test showed different patterns in releasing forces. A correlation was found between the DSC analysis and the three-point bending test results. Conclusion. The higher the temperature transformation was, the larger was the variation of force. All the wires presented higher forces at 3-mm deflection from 155 (±12.3) to 168.1 (±8) cN. The DSC analysis and the three-point bending test showed differences between the NiTi alloys from all the manufacturers.